1978
DOI: 10.1042/bj1730981
|View full text |Cite
|
Sign up to set email alerts
|

The effects of triton WR1339 and asialo-fetuin on the hepatic uptake of circulating native and asialo-carcinoembryonic antigen

Abstract: Uptake of carcinoembryonic antigen from the circulation of the mouse is inhibited by treatment of the animal with Triton WR1339, but not by asialo-fetuin. Uptake of asialo-carcinoembryonic antigen is inhibited by asialo-fetuin, but not by Triton WR1339. These results reflect the different mechanisms of uptake of the glycoproteins. The presence or absence of sialic acid does not seem to be important in governing Kupffer-cell uptake, but when terminal galactoses are exposed on a glycoprotein, uptake by hepatocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The clearance of intravenously injected enterokinase in this study was found to be similar to that described for the removal of other human glycoproteins such as carcinoembryonic antigen (Thomas & Jones, 1978), lymphoblastoid interferon (Bose & Hickman, 1977) and lactoferrin (Prieels et al, 1978). Clearance was rapid, with a serum half-life of only 2.5min and was not due to active-site recognition.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The clearance of intravenously injected enterokinase in this study was found to be similar to that described for the removal of other human glycoproteins such as carcinoembryonic antigen (Thomas & Jones, 1978), lymphoblastoid interferon (Bose & Hickman, 1977) and lactoferrin (Prieels et al, 1978). Clearance was rapid, with a serum half-life of only 2.5min and was not due to active-site recognition.…”
Section: Discussionsupporting
confidence: 82%
“…700-fold molar excess over enterokinase) and aggregated human immunoglobulin (approx. 2 x 104-fold molar excess) have been shown to be bound preferentially by Kupffer cells (Thomas & Jones, 1978;Embling et al, 1978). Asialoagalacto-fetuin (2.2x 10'-fold molar excess) contained terminal N-acetylglucosamine residues, since it was isolated by lectin-specific affinity chromatography, and glycoproteins containing this determinant have also been shown to be taken up by phagocytic cells (Stahl et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Competitive-inhibition studies with yeast mannan (terminal mannose), agalacto-orosomucoid (terminal N-acetylglucosamine) and ,B-glucuronidase (terminal mannose) showed that these compounds failed to inhibit carcinoembryonic antigen uptake in vivo (Table 1). Asialo-(carcinoembryonic antigen) is cleared from the circulation by the hepatocyte receptor for galactose (Thomas & Jones, 1978). Since native carcinoembryonic antigen was taken up by the Kupffer cell exclusively, and competition in vivo with asialofetuin (terminal galactose) failed to inhibit this process (Table 1) Time (min) Fig.…”
Section: Resultsmentioning
confidence: 99%